The association between perception of patients and their actual ability to do floor activities after mobile-bearing unicompartmental knee arthroplasty: A prospective, cross-sectional study - Narkbunnam R. (2023)
Objectives: This study aims to evaluate the association between patientsʼ perception and their ability to perform floor activities after mobile-bearing unicompartmental knee arthroplasty (MB-UKA). Patients and methods: This prospective, cross-sectional study included a total of 63 knees of 63 patients (7 males, 56 females; mean age: 65.6±6.2 years; range, 51 to 79 years) with anteromedial osteoarthritis knee who had MB-UKA with a follow-up period of at least one year postoperatively. Each participant was asked to rate their perception of their ability to perform six floor activities. Their actual abilities were measured by using a five-category anchored scale. The primary outcome was the association between participants’ perception and their actual ability. The secondary outcome was to evaluate factors affecting patients’ actual ability. Results: More than 60% of the patients could achieve good actual ability scores in performing chair kneeling, floor kneeling, and sitting side-legged regardless of their perception. Chair kneeling at 90 degrees had the most patients (69.8%) with good actual ability scores. Standing up from the floor was the activity with the highest positive perception rate of 84.1%. However, relatively lower actual activity scores were observed in floor squatting, cross-legged sitting, and standing up from the floor. Floor squatting yielded the lowest rate of positive perception and actual ability scores (39.1% and 20.6%, respectively). The Oxford Knee Score and knee flexion angle had moderate positive correlations with the actual ability scores (r=0.44 and 0.40, respectively). Conclusion: Patients’ perception and their actual ability may differ for each floor activity after MB-UKA. An appropriate sequence of activities based on their difficulties along with positive reinforcement and appropriate patient education may yield favorable functional outcomes following MB-UKA.